Adolescents' attitudes and intentions to use a smartphone app to promote safe driving. (March 2020) - Pope, Caitlin N.; Sezgin, Emre; Lin, Simon; Morris, Nichole L.; Zhu, Motao
Abstract: Purpose: Designing effective driving safety interventions is imperative as traffic crashes are the leading cause of injury and death for adolescents. Using concepts from the Integrated Behavioral Model, we investigated adolescents' attitudes and intentions towards engaging in safe driving practices and using smartphone-based driving safety technology. Methods: Two-hundred and seven adolescents aged 14–18 ( M = 16.1, SD = 0.8) completed a safe driving survey. A path model testing the associations between individual scores of attitudes, perceived norms, and perceived behavioral control with intentions controlling for demographic covariates was conducted. Results: Greater intentions to drive safely was associated with greater perceived norms from family and peers (β = 0.75, p < .001) and perceived capability (β = 0.19, p < .001) to drive safely. Greater intentions to adopt a driving safety app was associated with greater perceived norms from family and peers (β = 0.29, p = .007). Females reported greater intentions to adopt a driving safety app than males (β = −0.15, p = .044). Conclusions: Assessing attitudes and perceptions provides further understanding of what behavioral constructs are important for the development of adolescent driver safety interventions. Experimental research targeting and modifying behavior constructs is warranted. Highlights: Research on smartphone apps used to promote safe driving is promising but limited. Adolescents' intentions to use driving safety smartphone apps were assessed. Perceived norms had the strongest association with intentions. Females were more likely to report intentions to use a driving safety app.